Concept of Data Security in Digital Image Media Using Spread Spectrum Steganography and Playfair Cipher Cryptography - Natalinda Pamungkas; Bonifacius Vicky Indriyono; Ichwan Setiarso (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2024)
In the world of informatics, there are many techniques that can be used to maintain the confidentiality of digital information from parties who are not responsible and have access rights to that information. One of the most common techniques today is steganography and cryptography. Steganography is a method used to secure information by hiding it in an object without having to change the shape of the object, while cryptography is a science that studies the technique of encoding original text (plaintext) by utilizing encryption keys so that the script turns into text that is hard to read (ciphertext). ) by a user who does not have the decryption key. This research will explain how to secure information in digital images using spread spectrum steganography techniques and playfair cipher cryptography. The test results show that the information inserted in the digital image media is difficult to return to its original form and the media inserted does not change in size